PROTOGONIZATION OF THE SINGLE HEALTH SYSTEM IN THE COVID-19 PANDEMIC: : A REFLECTIVE STUDY FROM THE POINT OF PRIMARY HEALTH CARE - Christiny, Larissa; Alves Ribeiro, Wanderson; de Castro, Kemely; Motta Moreira de Souza, Érica; Santos Braz da Cunha, Vinícius; Kelly Souza Motta Alcoforado, Greyce; de Souza Rezende, George; Costa de Morais, Maicon; de Paula, Enimar; Silva Lima, Daiana (Health and Society, 2022)
Primary care is the main and preferred gateway to the SUS, being of fundamental importance for assistance to COVID-19 cases. Facing a pandemic requires that individual care be associated with community-centered care, requiring a population-based approach. This junction is essential to combat the current health and humanitarian crisis1. Health systems strongly based on Primary Health Care (PHC) can offer this comprehensive and articulated care, responding better to emergencies. The study aimed to reflect on the role of the Unified Health System in the COVID-19 pandemic, from the perspective of Primary Health Care. This is a descriptive, qualitative study of the reflective analysis type. Through the study, it was possible to perceive that the coronavirus pandemic quickly established itself as a serious public health problem due to its high potential for transmissibility, with this, the multiprofessional health teams played a great role in promoting education and information for the entire community. . And among health education activities, raising awareness of the need for all people to wear masks has saved many lives.